Cost Index dan Dampaknya Terhadap Efisiensi Biaya Operasional Pada B777-300 ER (Studi Kasus Garuda Indonesia) - Imam Ozali; Rudy Max Damara Gugat; Abi Prasidi (Institut Transportasi dan Logistik Trisakti, 2020)
In this challenging situations, Garuda Indonesia remains optimistic about the future by setting the direction of QuickWins strategy and the values of “One Family, One Nation, One GarudaIndonesia” in managing the company.These strategies have become the strong basis for GarudaIndonesia to develop and expand in the subsequent years. Thebusiness management in 2019 was also strengthened by the values of One Family, One Nation, One Garuda Indonesia, therefore, Garuda Indonesia could continue to provide the best service for Indonesia.Garuda Indonesia is also trying to implement the key work programs to develop revenue beyond the aviation business that would become a strong foundation for Garuda Indonesia to develop and expand in the next period. The purpose of the research is to determine the Cost Index and its impact on operational cost efficiency in B777-300ER (Garuda Indonesia case study). This research used the desciptive qualitative approach. The data was collected through observation, interview and documentation. The analysis technique used in this research was navblue cost index. The results of the study would be used to determine the extent of the cost index, the impact of increasing efficiency of B777-300ER operational costs, and in order to help companies making the right decision.